BENEFICIAL OWNERSHIP OF INCOME AS AN ANTIABUSIVE MEASURE IN SERBIAN TAX LAW - Vasović, Miloš (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Serbian domestic tax law on corporate income contains beneficial ownership of income provision (BO provision) which represents one of two terms for the use of preferential withholding tax rate from the application of double tax treaties (DTT). Subject of research is the undefined term „beneficial ownership“ in domestic tax law which can lead to „treaty shopping“ through the use of conduit companies. The BO provision is given function of an anti-abusive measure as well as an attribution of income rule. We will analyze the current function of BO provision given in Serbian tax law and its inadequate application. The author represents the stance of BO provision as an anti-abusive measure and examines the possible application of this provision in domestic law within articles 10, 11. and 12. of DTTs with regard to the same articles of OECD Model-Convention and Commentary, in order to prevent „treaty shopping“. At the end of this article, the author brings up the reasons why Serbia needs BO provision as an anti-abusive measure in its domestic tax law.